2021
DOI: 10.33963/kp.a2021.0023
|View full text |Cite
|
Sign up to set email alerts
|

Double chambered right ventricle in a patient with hypertrophic cardiomyopathy. A unique coexistence

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.Double chambered right ventricle in a patient with hypertrophic cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, DCRV complicated by HCM is an extremely rare coexistence. Several cases reported this unique condition complicated with HCM (2,5,6). With respect to the combination of arrhythmias, Alvarez et al reported that, in two adult patients diagnosed with DCRV, complicated by sustained monomorphic ventricular tachycardia, tachycardia did not reoccur after surgical excision of the abnormal muscle bundles (7).…”
Section: Discussionmentioning
confidence: 99%
“…However, DCRV complicated by HCM is an extremely rare coexistence. Several cases reported this unique condition complicated with HCM (2,5,6). With respect to the combination of arrhythmias, Alvarez et al reported that, in two adult patients diagnosed with DCRV, complicated by sustained monomorphic ventricular tachycardia, tachycardia did not reoccur after surgical excision of the abnormal muscle bundles (7).…”
Section: Discussionmentioning
confidence: 99%